2019
DOI: 10.22540/jfsf-04-030
|View full text |Cite
|
Sign up to set email alerts
|

Integrating functional ageing into daily clinical practice

Abstract: Health Organization (WHO) during the 54TH World Health Assembly on 22 May 2001 5 , and the 2015 WHO definition of healthy ageing as "the process of developing and maintaining functional ability which enables well-being in older age" 6 , this article aims to underscore, yet again, the importance of integrating daily functioning into the clinical practice of all health professionals caring for middle-aged and older adults. The personal life trajectory of these individuals is a unique and complex set of interming… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…It was believed that the hospital stay was prolonged because hospital admissions were due to complications and accompanying geriatric syndromes such as pressure sores and delirium were common in patients. Considering the increasing prevalence of chronic conditions with age and the occurrence of chronic conditions mostly in the elderly, it is believed that the progression of diseases and the development of complications may affect individual and social well-being by placing greater burdens on both the patients and the healthcare system (20).…”
Section: Discussionmentioning
confidence: 99%
“…It was believed that the hospital stay was prolonged because hospital admissions were due to complications and accompanying geriatric syndromes such as pressure sores and delirium were common in patients. Considering the increasing prevalence of chronic conditions with age and the occurrence of chronic conditions mostly in the elderly, it is believed that the progression of diseases and the development of complications may affect individual and social well-being by placing greater burdens on both the patients and the healthcare system (20).…”
Section: Discussionmentioning
confidence: 99%
“…The most widely used concept is the Fried physical frailty phenotype, which defines frailty based on three or more of the following five symptoms: unintentional weight loss, slowness, weakness, exhaustion, and low physical activity [5]. Yet, functional decline due to sarcopenia is in the core of frailty syndrome [6].…”
Section: The "Unhappy Triad"mentioning
confidence: 99%
“…Functional decline in ADL in elderly individuals cannot be attributed to a single domain [9][10][11]. Studies have demonstrated that lifestyle factors, including physical activity, diet, and smoking, are associated with functional ability in elderly people and may have positive/negative effects on functional disability [9][10][11]. Longitudinal studies have suggested that regular physical activity is associated with reduced mortality and risk of physical disability [12][13][14].…”
Section: Introductionmentioning
confidence: 99%